Does muscle coactivation influence joint excursions during gait in children with and without hemiplegic cerebral palsy? Relationship between muscle coactivation and joint kinematics. Issue 10 (December 2015) - Gross, Raphaël; Leboeuf, Fabien; Hardouin, Jean Benoit; Perrouin-Verbe, Brigitte; Brochard, Sylvain; Rémy-Néris, Olivier
Abstract: Background: The theoretical role of muscle coactivation is to stiffen joints. The aim of this study was to assess the relationship between muscle coactivation and joint excursions during gait in children with and without hemiplegic cerebral palsy. Methods: Twelve children with hemiplegic cerebral palsy and twelve typically developing children underwent gait analysis at three different gait speeds. Sagittal hip, knee, and ankle kinematics were divided into their main components corresponding to joint excursions. A coactivation index was calculated for each excursion from the electromyographic envelopes of the rectus femoris/semitendinosus, vastus medialis/semitendinosus, or tibialis anterior/soleus muscles. Mixed linear analyses of covariance modeled joint excursions as a function of the coactivation index and limb. Findings: In typically developing children, increased coactivation was associated with reduced joint excursion for 8 of the 14 linear models (hip flexion, knee loading, knee extension in stance, knee flexion in swing, ankle plantarflexion from initial contact to foot-flat, ankle dorsiflexion in stance and in swing). Conversely, ankle plantarflexion excursion at push-off increased with increasing tibialis anterior/soleus coactivation. In the involved limbs of the children with cerebral palsy, knee loading, ankle plantarflexion at push off, and ankle dorsiflexion in swing decreased, while hip extension increased, with increasing muscle coactivation. Interpretation: The relationships between muscle coactivation and joint excursion were not equally distributed in both groups, and predominant in typically developing children. The results suggest that excessive muscle coactivation is not a cause of stiff-knee gait in children with hemiplegic cerebral palsy, but appears to be related to spastic drop foot. Highlights: We investigated the relationship between muscle coactivation and joint excursions during gait. Children with hemiplegic cerebral palsy and typically developing peers underwent gait analysis. Mixed linear models were used to model joint excursions as a function of coactivation. Muscle coactivation was more associated with a reduction of the joint excursion in typically developing children.